Music to Make Your Mouth Water? Assessing the Potential Influence of Sour Music on Salivation - Wang, Qian J.; Knoeferle, Klemens; Spence, Charles (Frontiers in Psychology, 2017)
People robustly associate various sound attributes with specific smells/tastes, and soundtracks that are associated with specific tastes can influence people’s evaluation of the taste of food and drink. However, it is currently unknown whether such soundtracks directly impact the eating experience via physiological changes (an embodiment account), or whether they act at a higher cognitive level, or both. The present research assessed a version of the embodiment account, where a soundtrack associated with sourness is hypothesised to induce a physiological response in the listener by increasing salivary flow. Salivation was measured while participants were exposed to three different experimental conditions – a sour soundtrack, a muted video of a man eating a lemon, and a silent baseline condition. The results revealed that salivation during the lemon video condition was significantly greater than in the sour soundtrack and baseline conditions. However, contrary to our hypothesis, there was no significant difference between salivation levels in the sour soundtrack compared to the baseline condition. These results are discussed in terms of potential mechanisms underlying the auditory modulation of taste perception/evaluation.